2018
DOI: 10.1088/2053-1591/aaa567
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of small symmetrical and asymmetrical sized fullerene dimers

Abstract: Magnetism in carbon nanostructures is of high scientific interest, which could lead to novel magnetic materials. The magnetic properties of symmetrical and asymmetrical sized small fullerene dimers (C n for n≤50) have been investigated using spin polarized density functional theory. The interaction energies depict that small fullerene cages form stable dimer structures and symmetrical sized fullerene dimers are found more stable than asymmetrical sized dimers. The dimerization of fullerene cages in different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 56 publications
4
27
0
Order By: Relevance
“…Test calculations were performed on small fullerenes (Cn, n ≤ 40) and CNTs which are tabulated in Table 1. Our results are in good agreement with the previous studies [48][49][50].…”
Section: Computational Detailssupporting
confidence: 94%
See 2 more Smart Citations
“…Test calculations were performed on small fullerenes (Cn, n ≤ 40) and CNTs which are tabulated in Table 1. Our results are in good agreement with the previous studies [48][49][50].…”
Section: Computational Detailssupporting
confidence: 94%
“…5(d-e)). All The contribution from connecting bond atoms towards TMM is very small which may be due to sp 3 hybridization of completing their valency by make four σ-bonds with neighboring carbon atoms [48]. The Spin density plot ( Fig.…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we have reported a systematic study on symmetrical and asymmetrical‐sized small fullerene dimers, which are likely to be formed experimentally . Our results have shown that the formation of small fullerene dimers strongly depend on the type of interconnecting bonds between two cages.…”
Section: Introductionmentioning
confidence: 70%
“…There are four different modes through which fullerene cages can connect to form dimer structures . These four modes are: [1 + 1] point mode, [2 + 2] side mode, [5 + 5] face mode between two pentagon rings and [6 + 6] face mode between two hexagon rings .…”
Section: Resultsmentioning
confidence: 99%